Balance of Payments Statistics Yearbook, 2014. (Balance of Payments Statistics; Balance of Payments Statistics, 2014)
The Balance of Payments Statistics (BOPS) Yearbook provides tables of data, featuring regional and world totals of balance of payments and IIP components and aggregates as well as detailed information in the form of analytical and standard component presentations for economies. It is compiled in accordance with the IMF's Balance of Payments Manual (BPM6). The Balance of Payments Statistics Yearbook is usually published in December.